A Novel Steel Lazy Wave Riser Configuration for Ultra-Deepwater - Haoran, Chen; Karuppanan, Saravanan; Perumal, Veeradasan; Ovinis, Mark; Lim, Frank; Kumar, Suria Devi Vijaya (Salehan Institute of Higher Education, 2025)
A steel lazy wave riser (SLWR) configuration combines buoyancy modules with a traditional steel catenary riser (SCR). The buoyancy section at the riser separates the floater's motion and acts as a damper toward the critical area in the touchdown point, improving the strength and fatigue performance. In ultra-deepwater environments, the substantial payload of risers due to extreme riser length imposes considerable tension and stress, challenging the limits of traditional configurations such as SLWR and SCR. The effective tension, maximum stress, and minimum bend radius at ultra-deep depths of these conventional risers would exceed the allowable limits, leading to potential structural failure. To address these limitations, this study proposes a novel riser configuration, the shaped steel lazy wave riser (SSLWR), specifically for ultra-deepwater conditions. By introducing an additional buoy section, SSLWR effectively reduces the effective tension while ensuring allowable stress distribution across the riser length, enhancing structural reliability and operational feasibility over traditional risers. OrcaFlex, a fully 3D non-linear finite element software widely used in maritime structure analysis, was used to simulate the effective tension, maximum stress, and minimum bend radius of the SCR, SLWR, and SSLWR configurations at 3000 m depth. The SSLWR shows a maximum effective tension that is less than half of that observed in the SCR, and it remains consistently lower than SCR and SLWR, suggesting that SSLWR holds promise as a robust alternative for ultra-deepwater applications. This study offers new insights into how modifying riser shape and buoy placement can effectively balance tension reduction with stress distribution, providing an alternative to traditional riser designs. The SSLWR's specific responses to buoy placements and varying currents expand an understanding of riser performance under varying conditions, guiding future advancements in offshore riser engineering. Doi: 10.28991/CEJ-2025-011-01-03 Full Text: PDF